2011
DOI: 10.2527/jas.2010-3697
|View full text |Cite
|
Sign up to set email alerts
|

Bovine pyruvate carboxylase 5′ untranslated region variant expression during transition to lactation and feed restriction in dairy cows1

Abstract: Pyruvate carboxylase (PC; EC 6.4.1.1) is a critical enzyme for gluconeogenesis and maintenance of tricarboxylic acid (TCA) cycle intermediates, and expression of PC mRNA is increased at calving and during feed restriction. The bovine PC gene contains 3 promoters (3, 2, and 1 from 5' to 3') that produce 6 mRNA 5' variants (A through F). Products of promoter 1, untranslated region (UTR) variants A, B, C, and F are specifically expressed in glucogenic and lipogenic tissues. The objective of this study was to deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
18
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 34 publications
5
18
0
Order By: Relevance
“…Moreover, a negative correlation was observed between peripartum basal plasma insulin concentrations and the relative expression of PC (r = −0.85, P < 0.0001). These findings are in agreement with others (Graber et al, 2010;White et al, 2011), as the rate of hepatic gluconeogenesis must abruptly double during the peripartum period to meet the high glucose demand of the mammary gland (Bell and Bauman, 1997).…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, a negative correlation was observed between peripartum basal plasma insulin concentrations and the relative expression of PC (r = −0.85, P < 0.0001). These findings are in agreement with others (Graber et al, 2010;White et al, 2011), as the rate of hepatic gluconeogenesis must abruptly double during the peripartum period to meet the high glucose demand of the mammary gland (Bell and Bauman, 1997).…”
Section: Discussionsupporting
confidence: 92%
“…Given the regulation of hepatic PNPLA3 by FA in rodents and human hepatocytes (Huang et al, 2010), it is possible that bovine PNPLA3 is also responsive to FA, which are known to be dynamic during changes in energy balance in ruminant animals. Circulating NEFA concentrations were increased in both the feedrestricted cows (White et al, 2011a) and during +1 and +14 DRTC (Carvalho et al, 2011), as reported previously. Expression of PNPLA3 mRNA in each animal was negatively correlated with plasma NEFA concentration, with a modest, although significant rvalue of −0.33.…”
Section: Discussionsupporting
confidence: 87%
“…Liver biopsy samples from feed-restricted and transition cows were collected during experiments conducted at Purdue University (West Lafayette, IN). Full details regarding experimental design, methods, animal performance, and plasma NEFA have been reported previously (Carvalho et al, 2011;White et al, 2011a). Liver biopsy samples collected at −14, +1, +14, +28 d relative to calving (DRTC) in control-fed transition cows, and in mid-lactation cows after 5 d of ad libitum access to feed or 50% feed restriction were collected for isolation of RNA.…”
Section: Animal Handling and Sample Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Examination of the balance of PC and PEPCK during different physiological states or during nutritional challenges highlights the importance of anaplerotic balance. Increased hepatic expression of PC, but not PEPCK, is observed at calving [ 34 , 35 , 36 , 37 ] and may allow for increased oxidative capacity within the mitochondria. Regulation of PC during the transition to lactation is through regulation of PC Promoter 1, which is upregulated by fatty acids that mimic those in circulation at calving [ 32 , 35 , 38 , 39 ].…”
Section: Anaplerosis and Cataplerosis Of The Tca Cyclementioning
confidence: 99%